GOLDEN PROPORTION GIGI INICISIVUS SENTRAL RAHANG ATAS SUKU BALI DI FAKULTAS KEDOKTERAN GIGI UNIVERSITAS MAHASARASWATI DENPASAR - Norman Hidajah; Ketut Virtika Ayu; Dwis Syahrul (Interdental: Jurnal Kedokteran Gigi, 2020)
ABSTRACT Tooth size determines a person's aesthetics. Some guidelines that can help in determining the size of the maxillary anterior teeth are pre-extraction instructions such as facial photographs, diagnostic models, radiographic photographs, and extracted teeth. If the instructions before extraction are not obtained then an ideal proportionis needed. This study aims to determine whether or not thereis a relationship between the width and high of the face to the mesiodistal and cervico incisal of the maxillary central incisors and what is the proportion of these teeth. This research is a analytic observasional research with design of crosssectional, using samples of 47 subjects from Bali'sTrobe age 17_25 at Facultyof Dentistry in Unmas Denpasar. The resul to research show a significant correlation between face width and high to the size of mesiodistal and servico incisal of the maxillary centralincisorson Bali'sTrobe. The proportion of face and teeth of Balinese belonging to the Mongoloid race was obtain 1 :1,639 and mesiodistal and cervicoincisal of the maxillary central incisors where1 : 1,6409